The influence of the use of the SiANEH application on mothers’ independence in monitoring the growth and development of toddlers - Siregar, Nilda Yulita; Sembiring, Arihta Br.; Nasution, Eva Mahayani; Kurnia, Herni; Siregar, Siti Julianita Siregar (Poltekkes Kemenkes Bandung, 2026)
Background: Stunting is a significant health issue in Indonesia, affecting children's physical and cognitive development, as well as their future quality of life. One key strategy for preventing stunting is ensuring optimal monitoring of toddlers' growth and development. Objective: This study examined the impact of the Android application